(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Cosmic radiation is high-energy radiation generated in outer space that increases with altitudes. This study uses aircrew cosmic radiation exposure to measure radiation dose received by monitoring individual crew members (a total of 179 members for all the crews in the three routes for 2011 to 2022) using computer model calculator (CARI – 6M) on Nigeria’s local airlines crews and evaluated other radiological parameters. The finding shows that annual effective dose (AED) received by the air crew members between 2011 and 2022 across the three routes (Lagos – Kano, Lagos – Abuja and Lagos – Port Harcourt) ranges between 0.230 and 1.90 µSv y-1 and there is a direct relationship between the time of flight and the effective dose received by the crew members. This result is lower than the recommended value of 20 µSv y-1 by International bodies. The result also revealed that Annual Gonadal Dose Equivalent (AGDE) across the three routes ranges from 7.20 – 380 µSv y-1 with only Lagos – Kano route in year 2017 (380 µSv y-1) were above the maximum permissible value of 300 µSv y-1. The findings indicated low AED however; the significant excess lifetime cancer risk that increases with cumulative doses and dependent of the flight route constitute a risk. This implies that, there are possibilities of the crew members developing cancer during their lifetime. It’s therefore recommended that Nigerian Civil Aviation Authority should introduce regulations and training program to reduce potential sources of radiation exposure of Nigerian flight crews.